THE PERSPECTIVE DIRECTIONS OF USE OF THE METHOD OF THE MELT INTRA MOULD MODIFYING FOR PRODUCTION OF CASTINGS WITH THE SPECIFIED OPERATIONAL PROPERTIES - M. A. Fesenko; A. N. Fesenko (Литьë и металлургия)
On the basis of numerous studies using the methods of physical and simulation (computer) modeling, and also on the basis of the field experiments in the production of advanced and industrial castings prospective resource-saving technological areas of the method of in-mold inoculation of molten iron for castings with a given structure and propertiesis investigated in the work. The proposed areas can be recommended for implementation at enterprises of foundry industry for the manufacture of a wide range of high quality products.